Penulisan Surat Lamaran, Riwayat Hidup, Dan Surat Elektronik Untuk Pemuda/-I Karang Taruna RT 07/RW 005 Tanjung Barat - Engliana Engliana; Zumrotul Muniroh (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
This activity was carried out for youth organizations in the RT 007 RW 005 Tanjung Barat, Jagakarsa, South Jakarta. The purpose of holding this community service activity is to understand the community, especially youth organizations, in this case for those who are ready to enter the job market who demand to be able to make job application letters and curriculum vitae. The team employed the socialization method through the coaching technique for concept immersion. Direct and practical steps of writing were presented. The participants were able to write acceptable application letters and curriculum vitae emailed to the team. English is considered to be a compulsory foreign language that must be mastered to the ability of every resource to compete in the world of work; however, this language ability is still considered difficult for the wider community and becomes a burdensome condition even when they start making job application letters and tell their life history by using English.